Antibiotic Stewardship and Therapeutic Drug Monitoring of β-Lactam Antibiotics: Is There a Link? An Opinion Paper. Issue 1 (February 2022) - Richter, Daniel C.; Heininger, Alexandra; Chiriac, Ute; Frey, Otto Roman; Rau, Heike; Fuchs, Thomas; Röhr, Anka C.; Brinkmann, Alexander; Weigand, Markus A.
Abstract : Purpose: In critically ill patients, changes in the pharmacokinetics (PK) of β-lactams can lead to significant variations in serum concentrations, with possibly detrimental effects on outcomes. The utilization of individually calculated doses, extended infusion regimen, and therapeutic drug monitoring (TDM)-guided dose adjustments can mitigate the PK changes and help to achieve and attain an individual PK target. Methods: We reviewed relevant literature from 2004 to 2021 using 4 search engines (PubMed, Web of Science, Scopus, and Google Scholar). Unpublished clinical data were also examined. Results: TDM-guided, individualized dosing strategies facilitated PK target attainment and improved patient outcomes. TDM-guided therapy is a core concept of individualized dosing that increases PK target attainment and identifies possible toxic β-lactam concentrations. Conclusions: Individualized dosing and TDM facilitate the rational use of β-lactams and are integral for antibiotic stewardship interventions in critical care, affording the optimal exposure of both pathogen and drugs, along with enhanced treatment efficacy and reduced emergence of antimicrobial resistance.